Factors Related to Hearing Disorder on Traditional Fishermen in Namrole Sub-District South Buru Regency - asudin Sangaji1, Sahrir Sillehu2, M.Taufan Umasugi2, Ira Sandi Tunny2, Rapiah Sarfa Marasabessy3, Wa (Institute of Medico-legal Publications Pvt Ltd, 2020)
Namrole sub-district, South Buru regency, is one of the sub-districts in Maluku province where the majority of the people have a livelihood as fishermen. The process of fishing is done by diving using a compressor at depths exceeding 10 meters. This causes various complaints such as headaches, spasms and hearing disorder. The purpose of this study was to determine the factors associated with a hearing disorder in traditional fishermen. The research method used is quantitative descriptive. Statistical test results using the chi-square test showed that the depth of diving has a significant correlation with a hearing disorder with a value of ? = 0.01, while the period of work, duration of work, and frequency of diving do not correlate with the hearing disorder in traditional fishermen in Namrole district, South Buru Regency.